2013
DOI: 10.1177/0004563213505848
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular risk marker asymmetric dimethylarginine is elevated in asymptomatic, untreated HIV-1 infection and correlates with markers of immune activation and disease progression

Abstract: Background: As lifespan in HIV infection increases, cardiovascular disease has emerged as a cause of morbidity and mortality. Asymmetric dimethylarginine is an established marker of endothelial dysfunction and predicts cardiovascular events. The role of asymmetric dimethylarginine in HIV-related cardiovascular disease has not been established. Our aim was to determine whether asymmetric dimethylarginine concentrations were elevated in treatment naïve, HIV-infected subjects and to correlate these with markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
0
2
2
Order By: Relevance
“…Contrary to our findings, ADMA has been found to be higher in HIV-infected subjects versus controls in separate reports [10, 19]. The difference in mean ADMA reported between HIV-infected and HIV uninfected individuals has ranged between 0.03 μmol/L–0.18 μmol/L [10, 19, 20].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, ADMA has been found to be higher in HIV-infected subjects versus controls in separate reports [10, 19]. The difference in mean ADMA reported between HIV-infected and HIV uninfected individuals has ranged between 0.03 μmol/L–0.18 μmol/L [10, 19, 20].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, ADMA has been found to be higher in HIV-infected subjects versus controls in separate reports [10, 19]. The difference in mean ADMA reported between HIV-infected and HIV uninfected individuals has ranged between 0.03 μmol/L–0.18 μmol/L [10, 19, 20]. Mean levels of ADMA in HIV-infected individuals in our study was similar to what was found in previous reports of HIV-infected individuals who were ART-naïve and were younger than our patients [11, 19], however, levels in HIV-uninfected individuals were 0.18 umol/L higher in our study than what has been reported [19, 4].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, ADMA, a biomarker of endothelial dysfunction, is increased in patients with asymptomatic HIV infection (79), and could be posited associate with disruption of the blood brain barrier and HAND. While the role of ADMA remains unknown, this is one of a group of novel biomarkers which need to be explored to optimize assessment of HIV and guide HIV care, particularly in patients at risk for HAND.…”
Section: Introductionmentioning
confidence: 99%